A Review on Green Building vs. Green Construction: Key Differences, Benefits, Challenges, Rating, and Future OutlookGreen Building vs. Green Construction: Exploring Key Differences and Challenges for a More Sustainable Industry (A Narrative Review) (International Journal of Built Environment and Sustainability, 2025)
The construction industry is a major contributor to a country’s Gross Domestic Product; however, construction activities also result in high greenhouse gas emissions, energy consumption, and waste generation that negatively impact the environment. To overcome these practices, sustainable development has become a popular concept, with Green Building and Green Construction introduced to promote sustainability in the construction industry. This review aims to address critical research questions distinguishing the concepts of Green Construction and Green Building, providing a better understanding of green practices in the construction industry, including the key definitions and concepts that contribute to sustainable development and environmental protection. Additionally, this study explores the differences and similarities between Green Construction and Green Building, operationalising them and discussing the implications they have for building and construction practices. Furthermore, the review highlights the key drivers and challenges for establishing the terms Green Building and Green Construction, as well as their broader societal goals such as sustainability and environmental protection. This review also examines the benefits and drivers of green practices implementation in the industry, and recognises the development of established green rating systems to evaluate the green measures of building projects. By shedding light on these aspects, this study will enable stakeholders and key players in the industry to pay more attention and take proactive actions towards the future direction of sustainable development.
Keywords: Sustainability, Green construction, Green building, Construction industry.